3T MR-defecography—A feasibility study in sensorimotor complete spinal cord injured patients with neurogenic bowel dysfunction. Issue 91 (June 2017) - Putz, Cornelia; Alt, Celine D.; Hensel, Cornelia; Wagner, Björn; Gantz, Simone; Gerner, Hans-Jürgen; Weidner, Norbert; Grenacher, Lars
Graphical abstract: Highlights: MR-defecography is feasible in complete paraplegic spinal cord injured patients. With an adopted preparation, standard sequences for MR-defecography can be used. MR-defecography may support neurogenic bowel dysfunction treatment decisions. Abstract: Introduction: To investigate whether MR-defecography can be employed in sensorimotor complete spinal cord injury (SCI) subjects as a potential diagnostic tool to detect defecational disorders associated with neurogenic bowel dysfunction (NBD) using standard parameters for obstructed defecation. Material and methods: In a prospective single centre clinical trial, we developed MR-defecography in traumatic sensorimotor complete paraplegic SCI patients with upper motoneuron type injury (neurological level of injury T1 to T10) using a conventional 3T scanner. Defecation was successfully induced by eliciting the defecational reflex after rectal filling with ultrasonic gel, application of two lecicarbon suppositories and digital rectal stimulation. Examination was performed with patients in left lateral decubitus position using T2-weighted turbo spin echo sequence in the sagittal plane at rest (TE 89 ms, TR 3220 ms, FOV 300 mm, matrix 512 × 512, ST 4 mm) and ultrafast-T2-weighted-sequence in the sagittal plane with repeating measurements (TE 1.54 ms, TR 3.51 ms, FOV 400 mm, matrix 256 × 256, ST 6 mm). Changes of anorectal angle (ARA), anorectal descent (ARJ) and pelvic floor weakness were documented and measured data was compared to reference values of asymptomatic non-SCI subjects in the literature to assess feasibility. Results: MR-defecography provides evaluable imaging sequences of the induced evacuation phase in SCI patients. Measurement results for ARA, ARJ, hiatal width (H-line) and hiatal descent (M-line) deviate significantly from reference values in the literature in asymptomatic subjects without SCI. The overall mean values in our study for SCI patients were: ARA (rest) 127.3°, ARA (evacuation) 137.6°, ARJ (rest) 2.4 cm, ARJ (evacuation) 4.0 cm, H-line (rest) 7.6 cm, H-line (evacuation) 8.1 cm, M-line (rest) 2.6 cm, M-line (evacuation) 4.2 cm. Conclusions: MR-defecography is feasible in sensorimotor complete SCI patients. Individual MR-defecography findings may help to determine specific therapeutical options for respective patients suffering from severe NBD.